Local aggregation effect of CNT on the vibrational behavior of four‐parameter continuous grading nanotube‐reinforced cylindrical panels. Issue 5 (2nd April 2013) - Pourasghar, A.; Yas, M.H.; Kamarian, S.
Abstract Free vibrations analysis of four‐parameter continuously graded nanocomposite cylindrical panels reinforced by randomly oriented straight and local aggregation single‐walled carbon nanotubes (CNTs) are presented based on three‐dimensional theory of elasticity. The material properties of continuously graded carbon nanotube‐reinforced composites (CG‐CNTRCs) are estimated through the Eshelby–Mori–Tanaka approach based on an equivalent fiber. The generalized differential quadrature method as an efficient and accurate numerical tool is used to discretize the governing equations and impediment the boundary conditions. One of the contributions of this work is to illustrate the influence of the four parameters of power‐law distributions on the vibration behavior of functionally graded orthotropic cylindrical panels reinforced by nanotube. The properties of CG‐CNTRC are affected by its microstructure, especially the degree of CNT aggregation that is described by an aggregation coefficient. It is shown the degree of aggregation canseriously reduce the effective stiffness and frequency parameter. POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers